Pengaruh Parameter Proses Pada 3D Printing FDM Terhadap Kekuatan Tarik Filament ABS CCTREE - Pristiansyah Pristiansyah; Hasdiansah Hasdiansah; Ade Ferdiansyah (Manutech : Jurnal Teknologi Manufaktur, 2022)
3D printing technology is one of the new breakthroughs in the world of manufacturing. This principle uses layered modeling, which directly converts 3D data from computer-aided design (CAD) into physical prototypes. Additive Manufacturing technology itself has attracted a lot of interest as research material from industry to academia because it can provide manufacturing solutions that produce products with complex designs and reduce time without compromising print quality. Currently, the Fused Deposition Modeling (FDM) process is the most widely used process in 3D printing due to its ease of operation, low operating costs and environmental convenience. This study uses the Taguchi method with quality characteristics the bigger the better. The experimental design used is L27 OA by analyzing the Signal to Noise Ratio SNR. The method is based on the principle of tensile strength, to determine the process parameters that greatly affect the ABS CCTREE filament. The process parameters used in this research are nozzle temperature, layer thickness, temperature based plate, print speed and infill pattern. The order of the most influential parameters in a row is layer thickness of 40,74%, print speed of 9,40%, nozzle temperature of 5,69%, temperature based plate of 5,56% and infill pattern of 4,36%.